Structural Determinats of Educational Disparities in ASEAN: A Cross-National Policy Analysis - Muhammad Haizul Falah (International Journal of Educational Evaluation and Policy Analysis, 2026)
Educational inequality persists across ASEAN despite improvements in enrollment and literacy, reflecting structural rather than merely access-related challenges. This study examines how governance structures, financing mechanisms, institutional capacity, and socio-economic stratification interact to produce disparities in educational access, participation, and progression. Using a qualitative-dominant mixed-methods design with cross-national comparative policy analysis, the research integrates macro-level quantitative indicators with in-depth qualitative evaluation of policy frameworks across ASEAN member states. Findings reveal that while primary enrollment approaches universality, secondary and tertiary education exhibit pronounced attrition, particularly among rural, low-income, and minority populations. Centralized governance, equitable public financing, and targeted support correlate with higher retention and reduced disparities, as evidenced in high-performing systems such as Singapore, whereas decentralized or under-resourced systems exacerbate structural inequities. Moreover, digital access and institutional capacity emerge as critical factors influencing educational trajectories. The study underscores that addressing inequality requires systemic reforms integrating governance coordination, progressive financing, institutional strengthening, and equity-focused interventions. By foregrounding structural determinants and cross-national variation, this research contributes to theoretical and policy debates on educational equity, providing evidence-based guidance for ASEAN strategies aimed at achieving inclusive, high-quality education across diverse socio-economic and geographic contexts.